VARIABILITY OF NUCLEOTIDE AND AMINO ACID SEQUENCES OF HORDOINDOLINE GENES IN COLLECTION OF SPRING BARLEY FROM KAZAKHSTAN - Volkova, L.; Abugalieva, S.; Turuspekov , Y. (Eurasian Journal of Applied Biotechnology, 2014)
Grain hardness is an important trait of quality in cereal crops. Samples with harder grains are more favorable for animal feeding forms, while samples with softer grains are more useful for breeding of malting barley. In barley Hordeum vulgare L. this trait is associated with availability and variability of tryptophan rich polypeptides, which called hordoindolines (HIN). Hordoindoline coding genes (Hin) are homologs of puroindoline genes (Pin) of wheat and genetically mapped in short arm of chromosome 7 (5H) of barley genome. The family of hordoindoline genes consists from Hina, Hinb1, Hinb2, and Gsp, where first three genes are most functionally important and directly related to the level of barley grain hardness. In this work we report on variability of nucleotide sequences of Hin genes in collection of two-rowed spring barley of Kazakhstan, which consisted from 96 cultivars and perspective lines that were collected from six different breeding organizations across the country. Identified allelic variants of Hina, Hinb-1, and Hinb-2 suggest availability of 2, 3, and 5 isoforms for each peptide, respectively. Studied cultivars and perspective lines have been characterized for each of those three genes both for nucleotide and amino acid sequences. Also, the groups of samples with different haplotypes that separated based on analysis of all three genes were identified. Comparative genetic and phylogenetic analyses of local and previously described foreign barley samples were conducted based on nucleotide and amino acid sequences of three Hin genes. The average genetic diversity of barley samples from Kazakhstan for all three genes Hina, Hinb-1 and Hinb-2 (0.3929, 0.3776, 0.3525) was lower than those in world barley collection. The differences on clasterization of all three proteins (HINA, HINB-1 and HINB-2) were determined based on analysis of phylogenetic trees. The results of this work can be used in breeding projects related both to development of feeding and malting barley.